The analysis and modeling of the feedback process of the labor market: a dynamic model on Portugal’s national economy - Popescu, B.; Vale, S.; Chirita, N. (Journal of Economic Computation and Economic Cybernetic Studies and Research, 2015)
The present paper proposes a system dynamics approach to the feedback process of the labor market taking place at macroeconomic level. The model was constructed on Keynesian theory introducing into the model adjustment by quantity and the wage was modeled as an endogenous state variable. The objective of studying the functioning of the presented feedback process is that of understanding its role and effect in the real economy cybernetic system in order to make it a functional part of the system of models that capture the national economy as a whole to be used in macroeconomic governance. The analysis and simulations of the model were done on Portugal’s national accounts between 2005 and 2011 and the model is able to produce the behavior in time of the state variables wage and unemployed persons close to historical data.